The idea of a virtuous person in the legacy of al-Farabi and Turkic scholars - Omirbekova, A.; Duisenbayev, A.; Baltymova, M. (Eurasian Journal of Religious Studies, 2023)
Today, the idea of a virtuous person in the legacy of al-Farabi and Turkic scholars is one of the most topical challenges. Above all, the intensive social development of our society places high demands on the formation of an active, creative personality. And the current status of society, with the renewal of the political, cultural, socio-economic aspects of the country, the development of the younger generation as a respectable citizen will undoubtedly be greatly influenced by their proper personality formation. Thus, the analysis of theoretical research, the general concept of personality is considered in various fields of science. A virtuous person is the result of moral education in socio-historical development. The formation of personality occupies an important place for the characterization of a person, that is, it provides highly conscious forms of his behavior and actions, forming the unity of all his relations with reality. This point of view formed the basis of most studies. The authors consider values oriented towards a virtuous person (motives and needs, aspirations and demands, virtue and mercy, etc.) based on the heritage of Turkic scholars. Thus, a virtuous person in the heritage of Al-Farabi and Turkic scholars is, first of all, an individual as a subject of social interaction and conscious action. Secondly, it is a systematic estate of the individual, determined by his inclusion in social relations and is the basis for the syncretism of religious education. Key words: Turkic scholars, values, religious education, personality, virtuous person.